Tourism Potential of the Territory and His Development as the Basis for Youth Events: Potensi Pariwisata Wilayah dan Perkembangannya sebagai Dasar Acara Remaja - Fomenko, Vita Alexandrovna (Indonesian Journal of Law and Economics Review, 2020)
The article is devoted to the study of the urgent topic of the development of tourism potential as a basis for youth events. A model of the system of tourism potential components is presented, which includes the natural resource potential of the tourism sector, historical and cultural potential, infrastructure potential, financial potential, information potential, investment potential, managerial potential, social potential of the tourism sector, labor potential. Due to the fact that the tourism potential of the territories is a system, its main features are distinguished: dynamism, hierarchy, ability to transform, inversion, development, etc. Due to the fact that at the present stage, potential management problems are becoming more complicated, included in the tourist potential of the territories, the management of territories in the field of tourism development, including its potentials, should develop as a synthesis of two aspects: improving scientific and practical activities and developing management phenomena as art. A special role is given to youth events, highlighting the largest and most important ones that are developing in certain parts of Russia. These regions have the most powerful tourism potential and tourist infrastructure.